PRACTICES OF ONLINE MEDIA CONGLOMERATION - Efriyandi Efriyandi; Anis Endang SM; Indria Indria (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
In this era of globalization, the need for information is fast becoming very important for society. With this speed, online media has become one of the mass media that has a lot of interests and readers. On the other hand, it also gave birth to business interest for capital owners to establish large online media such as more than one, making the practice of conglomeration. As in Vicent Mosco's theory the conglomeration is a merging of a media company into a larger company that is in charge of the media. Ultimately, it also had an impact on reporting to the public and evidenced by conducting research on qualitative methods, namely by conducting interviews, observation and documentation with Miles model analysis techniques to media owners as well as to online media reporters SMSI group. In-depth interviews with discussions that have been determined previously in order to obtain data on this study. From this practice that there is a lot of space played by media owners, one of whom occupies as the editor and as the leader of the media, then all practical policies are all determined by the editor of good news that will be covered by journalists in the field. Technically, all news has been conceptualized by the editor, such as issues that will become news. Issues raised provide opportunities for journalists or media owners to find income for companies, such as cooperation with the government or political figures and the news is one of the priorities of the conceptual media owner.